Experimental Infections of Pigs with Japanese Encephalitis Virus Genotype 4 - Paul M. Hick; Deborah S. Finlaison; Kate Parrish; Xingnian Gu; Philip Hayton; Tiffany O’Connor; Andrew Read; Jing Zhang; Zoe B. Spiers; Pedro Pinczowski; Angel L. Ngo; Peter D. Kirkland (Microorganisms)
The emergence of Japanese encephalitis virus (JEV) in eastern Australia in 2022 caused extensive reproductive disease in pigs and is a threat to public health. Groups of weaned piglets were experimentally infected with the Australian outbreak strain of JEV (genotype 4). All pigs challenged at 5 weeks of age were infected after an intradermal injection of 1 × 105.5 (n = 4) or 1 × 104.5 TCID50/pig (n = 5). Intranasal instillation was less effective at this age, infecting 3/4 pigs with the same higher dose and 1/5 with the lower dose. Intradermal injection using 1 × 105.0 TCID50/pig also infected 9/9 pigs at 11 weeks of age. Infection in all cases was confirmed by qRT-PCR of blood samples, which identified a viremia peak at 3–4 days and detected JEV-specific antibodies as early as 5 days after the challenge. The detection of JEV in oral and nasal swabs and in saliva from chew ropes was less consistent. JEV was detected in the tonsils of 21/22 infected pigs and was isolated from the tonsils of 9/9 pigs sampled 19 days after the challenge at 11 weeks of age. The infected pigs showed no clinical signs other than pyrexia on Days 4–6. Histopathology consistent with JEV infection was evident in the nervous tissues of all but two pigs sampled 28 days after the challenge and was characterized by meningitis, encephalitis and gliosis throughout the brain. Serological studies showed extensive cross-reactivity between JEV and Murray Valley encephalitis virus using blocking ELISAs. However, the determination of limiting-dilution titres allowed for the identification of the infecting virus. This in vivo infection model will be useful in evaluating JEV vaccines and for comparative pathogenesis studies with other JEV genotypes.